The role of a peri-urban forest on air quality improvement in the Mexico City megalopolis (2012)
Air quality improvement by a forested, peri-urban national park was quantified by combining the Urban Forest Effects (UFORE) and the Weather Research and Forecasting coupled with Chemistry (WRF-Chem) models. We estimated the ecosystem-level annual pollution removal function of the park’s trees, shrub and grasses using pollution concentration data for carbon monoxide (CO), ozone (O3), and particulate matter less than 10 microns in diameter (PM10), modeled meteorological and pollution variables, and measured forest structure data. Ecosystem-level O3 and CO removal and formation were also analyzed for a representative month. Total annual air quality improvement of the park’s vegetation was approximately 0.02% for CO, 1% for O3, and 2% for PM10, of the annual concentrations for these three pollutants. Results can be used to understand the air quality regulation ecosystem services of peri-urban forests and regional dynamics of air pollution emissions from major urban areas.